PENGARUH MODEL PjBL (PROJECT BASED LEARNING) BERBANTUAN MEDIA AUDIO VISUAL TERHADAP KETERAMPILAN MENULIS ARTIKEL MAHASISWA PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS EKASAKTI PADANG - Khairani, Zuraida; Hayati, Najmi; Chan, Dwi Mutia (STKIP Pesisir Selatan, 2024)
The aim of the research is to describe the article writing skills of students at the Language and Literature Education Study Program at Ekasakti University in Padang before and after the implementation of the PjBL (Project Based Learning) model assisted by audio visual media and to analyze the effect of implementing the PjBL (Project Based Learning) model assisted by audio visual media on article writing skills Students of the Language and Literature Education Study Program, Ekasakti University, Padang. This type of research is quantitative research with experimental methods. The results of this research are that students' article writing skills before applying the PjBL model assisted by audio-visual media obtained an average of 65.00, students' article writing skills after applying the PjBL model assisted by audio-visual media, the highest score obtained was an average of 78.58, applying the PjBL model with the help of audio visual media, after carrying out the t-test, it was obtained that tcount > ttable or 3.27 > 1.70. So H0 is rejected and H1 is accepted. This means that the application of the PjBL model assisted by audio-visual media is feasible to apply to the article writing skills of students at the Language and Literature Education Study Program, Ekasakti University, Padang.